2011
DOI: 10.2147/nsa.s19419
|View full text |Cite
|
Sign up to set email alerts
|

Titanium dioxide and zinc oxide nanoparticles in sunscreens: focus on their safety and effectiveness

Abstract: Sunscreens are used to provide protection against adverse effects of ultraviolet (UV)B (290-320 nm) and UVA (320-400 nm) radiation. According to the United States Food and Drug Administration, the protection factor against UVA should be at least one-third of the overall sun protection factor. Titanium dioxide (TiO2) and zinc oxide (ZnO) minerals are frequently employed in sunscreens as inorganic physical sun blockers. As TiO2 is more effective in UVB and ZnO in the UVA range, the combination of these particles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
480
1
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 812 publications
(539 citation statements)
references
References 109 publications
5
480
1
7
Order By: Relevance
“…This manuscript supports the observation that actually the antibacterial features may not be a direct result of the presence of TiO 2 but a consequence of ROS interacting with the membrane of bacteria. A better knowledge of the interactions between TiO 2 (or ZnO), electromagnetic radiation, and water is mandatory in understanding the chemical processes and risks implied by the use of sunscreens and/or cosmetics based on oxide semiconductors [28]. Recent studies suggest that sonication can replace the electromagnetic radiation in the generation of ROS in TiO 2 [17,29].…”
Section: Initiation (Production Of Radicals)mentioning
confidence: 99%
See 1 more Smart Citation
“…This manuscript supports the observation that actually the antibacterial features may not be a direct result of the presence of TiO 2 but a consequence of ROS interacting with the membrane of bacteria. A better knowledge of the interactions between TiO 2 (or ZnO), electromagnetic radiation, and water is mandatory in understanding the chemical processes and risks implied by the use of sunscreens and/or cosmetics based on oxide semiconductors [28]. Recent studies suggest that sonication can replace the electromagnetic radiation in the generation of ROS in TiO 2 [17,29].…”
Section: Initiation (Production Of Radicals)mentioning
confidence: 99%
“…The large absorbance of TiO 2 in UV is widely recognized and documented. Micron sized TiO 2 particles are efficient in blocking UVB type of radiation while micron sized ZnO nanoparticles are preferentially absorbing in UVA-1 domain [28]. Nevertheless, as the UV radiation is absorbed, electron-hole pairs are generated and ROS production is ignited in both ZnO and TiO2 particles.…”
Section: Potential Biological and Medical Applicationsmentioning
confidence: 99%
“…Metal nanoparticles such as silver, titanium, zinc, and aluminum are widely used. For example, zinc nanoparticles (Zn-NPs) and titanium nanoparticles (Ti-NPs) are currently used in sunscreen cosmetics for the prevention of ultraviolet (UV) radiation-induced dermal diseases, including carcinoma and burns (Monteiro-Riviere et al, 2011, Smijs andPavel, 2011, Nohynek andDufour, 2012). However, previous studies have shown that metal nanoparticles induced DNA damage and oxidative stress in keratinocytes (Shukla et al, 2011), hepatoma cells (Kim et al, 2009) and lung epithelial cells (Limbach et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these are also being used in solar-cell, photovoltaics, piezo-electronic devices [7,8]. Amongst several metal oxides, zinc oxide, and titanium oxide are very commonly used in sunscreens and cosmetics [9][10][11][12][13]. With the increasing production and use of nanomaterials, their inevitable release to the environment increases.…”
Section: Introductionmentioning
confidence: 99%